Danshen (Salvia miltiorrhiza) on the Global Market: What Are the Implications for Products’ Quality? - Kum, Ka Yui; Kirchhof, Rainer; Luick, Rainer; Heinrich, Michael (Frontiers in Pharmacology, 2021)
Background Danshen (Radix et rhizoma Salviae miltiorrhizae Bunge, Lamiaceae) is commonly used in Asian countries. It is included in multiple pharmacopeias and standardised using salvianolic acid B and tanshinone IIA. However, on the markets, substitutes and different processing methods can be found. This results in ambiguities regarding the authentication and quality of Danshen, an essential basis for safety and effects. Aims This study aims at understanding the quality of Danshen derived products on the market and assessing the potential of developing more integrated analytical method for quality control. Methods Inductively coupled plasma optical emission spectrometry was used to understand the heavy metal content while high-performance thin-layer chromatography and proton nuclear magnetic resonance coupled with principal component analysis were used to understand the variation of metabolite composition among Danshen derived products. MTT and LPS induced NO production assays were used to evaluate the cytotoxicity and anti-inflammation activity, respectively. Result and Discussion Six out of sixty samples exceed the limits of cadmium. Arsenic, lead and copper contents are all below pharmacopoeial thresholds. When the complexity of the processing procedure increases, the possibility of heavy metal contamination increases. The metabolite compositions show a correlation to processing and storage methods. Authenticated samples and Vietnamese primary samples contain higher salvianolic acid B, and the chemical compositions are more consistent compared to the samples from Chinese online stores. The results show that a significant chemical variation can be observed Danshen products, which directly relates to the processing and storage method instead of geographical origins. In the MTT assay, fourteen samples show cytotoxicity while seven samples increase the proliferation of RAW264.7. In the LPS induced NO production of RAW 264.7, only seven samples show significant inhibitory effects. Conclusion This is the first interdisciplinary investigation focusing on understanding the current market and quality of Danshen. Danshen derived products are generally safe, but quality varies. The bioassay approach selected does not correlate with the PCA pattern and is not useful to differentiate products. Overall, this approach highlights the tremendous variability of the products along different value chains and the need for more systematic and stringent quality assurance.